Liver parenchymal changes detected by MR elastography and diffusion-weighted imaging after stereotactic body radiotherapy for hepatocellular carcinoma. - Omiya, Yoshie; Morisaka, Hiroyuki; Matsuda, Masaki; Saito, Masahide; Hashimoto, Takaaki; Motosugi, Utaroh; Onishi, Hiroshi (Abdominal Radiology, 2023)
Background: Stereotactic body radiotherapy (SBRT) is a local treatment option for hepatocellular carcinoma (HCC). SBRT-induced focal reactions on the liver parenchyma have not been thoroughly evaluated using quantitative magnetic resonance imaging (MRI). Purpose: To quantitatively evaluate liver parenchymal changes caused by SBRT for HCC using magnetic resonance elastography (MRE) and diffusion-weighted imaging (DWI). Method: We retrospectively evaluated 22 adult patients who received SBRT for HCC and 27 who received locoregional therapy other than SBRT (controls). Liver stiffness by MRE and apparent diffusion coefficient (ADC) values by DWI of the liver parenchyma were measured before and after SBRT. Regions of interest (ROIs) were drawn on the two areas of radiation dose distribution levels, > 30 Gy and ≤ 30 Gy; a ROI was drawn in the control group. The two indices were compared before and after SBRT using a Wilcoxon matched-pairs signed-rank test. Results: Liver stiffness and ADC values were significantly increased after SBRT in the dose areas of > 30 Gy compared with those before SBRT (4.05 vs 4.85 kPa; p < 0.05 in liver stiffness, and 1.10 vs 1.40 ×10−3 s/mm2; p < 0.05 in ADC values). In the dose area of ≦ 30 Gy, liver stiffness showed a significant increase in one reader (p = 0.033) but not in another reader (p = 0.085); ADC value showed no significant difference before and after SBRT as per both readers (p > 0.05). The control group demonstrated no significant differences before and after treatment (p > 0.05). Conclusion: MRE and DWI can be used to detect SBRT-induced liver parenchymal changes.